A wild barley nested association mapping population shows a wide variation for yield-associated traits to be used for breeding in Australian environment - Anh-Tung Pham; Andreas Maurer; Klaus Pillen; Trung Dzung Nguyen; Julian Taylor; Stewart Coventry; Jason K. Eglinton; Timothy J. March (Euphytica, 2024)
This study aimed to identify wild barley alleles controlling grain size and weight with the potential to improve barley yield in Australia and worldwide. The HEB-25 nested association mapping population was used, which samples 25 different wild barley accessions in a ‘Barke’ genetic background. The HEB-25 population was evaluated in field conditions at Strathalbyn in South Australia in 2015 and 2016. Seven yield component traits reflecting ear length, grain number per ear and grain dimension were measured. Among 114 quantitative trait loci (QTL) identified for the seven traits in both years, many co-localise with known genes controlling flowering and spike morphology. There were 18 QTL hotspots associated with four loci or more, of which one at the beginning of chromosome 5H had wild alleles that increased both grain number per ear and thousand-grain weight. A wide range of effects was found for wild alleles for each trait across all QTL identified, providing a rich source of genetic diversity that barley breeders can exploit to enhance barley yield.